Representasi Afrika dalam Lagu “Do They Know It’s Christmas?” oleh Band Aid” (1984) - Yuana, Made Tarita Kezaravijaya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Brawijaya, 2024)
The relationship between popular culture and world politics is an exciting study in the study of International Relations. One of the products of popular culture is a song. This article will examine one of the charity songs for famine in Ethiopia entitled